2015
DOI: 10.3390/agronomy5040476
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Sorghum, Groundnut, Sesame, and Cowpea to Seed Priming and Fertilizer Micro-Dosing in South Kordofan State, Sudan

Abstract: This study was undertaken with the objective of evaluating micro-dosing of mineral fertilizer combined with seed priming in sorghum, groundnut, sesame, and cowpea. On-station and on-farm trials were conducted for two consecutive seasons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
(22 reference statements)
2
12
0
Order By: Relevance
“…This combination in turn further reduce the vulnerability of maize to the impact of rainfall variability and terminal drought in the central Rift Valley. These results are consistent with other results that seed priming and fertilizer micro‐dosing improves agronomic and economic returns of millet in low‐rainfall regions of Mali (Aune et al, ), of sorghum, sesame, groundnut, and cowpea in the semi‐arid Sudan (Abdalla et al, ), and of maize in semi‐arid Ethiopia (Sime & Aune, ). Since seed priming reduces the risk of crop failure, it could therefore improve the interest of farmers to use fertilizers in maize production, with the combination being a preferable option.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This combination in turn further reduce the vulnerability of maize to the impact of rainfall variability and terminal drought in the central Rift Valley. These results are consistent with other results that seed priming and fertilizer micro‐dosing improves agronomic and economic returns of millet in low‐rainfall regions of Mali (Aune et al, ), of sorghum, sesame, groundnut, and cowpea in the semi‐arid Sudan (Abdalla et al, ), and of maize in semi‐arid Ethiopia (Sime & Aune, ). Since seed priming reduces the risk of crop failure, it could therefore improve the interest of farmers to use fertilizers in maize production, with the combination being a preferable option.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in the central Rift Valley of Ethiopia showed that seasonal rainfall is highly unpredictable and variable with high risks of crop failure and low productivity (Belay et al, ), which escalates farmers’ risk‐averse behavior, discouraging them from investing in expensive fertilizers (Kassie et al, ). Previous studies concluded that on‐farm seed priming is a simple, low cost, low risk intervention that represents a good insurance for risk‐averse, resource‐poor farmers (Abdalla et al, ; Aune & Ousman, ; Camara et al, ; Hayashi et al, ; Osman et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the related cereal species, Sorghum, a recent study in Sudan (at 12°N) found a manifest effect on yield (27% to 76% increase) using hydropriming of seeds in areas having around 600 mm annual rainfall; the strongest effect was observed in plots also receiving a high dose of mineral fertilizer, and all seeds were treated with pesticide after drying (Abdalla et al, 2015). All the three aforementioned studies, have applied 8 h of soaking and 1 to 2 h for drying of seeds.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%